THE THEORETICAL BASIS OF THE EXPERIMENTAL TEACHING METHODS OF TECHNICAL-TACTICAL ACTIONS IN KARATE-DO - Vasiliy Zubenko; Vladimir Magin; Victor Mashchenko (Вестник Северо-Кавказского федерального университета)
The article presents the results of theoretical research, which allowed the authors to construct the experimental teaching methods of technical-tactical actions in karate-do and to reveal its conceptual nature. The experimental technique is based on the didactic principles of teaching, adapted to the process of teaching athletes the technical and tactical actions in karate and developed his project and the semantic structure. This technique is of pedagogical value for sports science and training of high-class athletes.